Pendekatan Lean Manufacturing Dengan Value Stream Mapping (VSM) Dan Kaizen Pada Proses Produksi Tas Kulit - Parwati, Cyrilla Indri; Arsa, I Wayan Adi; Sodikin, Imam (Nusantara of Engineering (NOE), 2023)
The production process is said to be efficient and effective if the process does not produce waste or waste, but in reality a company in carrying out its production process cannot be separated from waste. PT. Mandiri Jogja Internasional is an industry engaged in manufacturing, with production in the form of leather products, namely leather bags, leather shoes, leather wallets and others. In the process there is still waste as indicated by the large number of raw materials in the process of work scattered on the floor, there are still tools and materials that have not been considered by employees for storage, there is waiting time for sewing work, and there are old raw materials that have not been used. The existing waste must be minimized and eliminated so as not to harm the company. This study uses lean manufacturing with value stream mapping and kaizen to minimize waste and implement 5s. The results obtained by waste that often occur in the leather bag production process are overprocessing 3, transportation 1.8, waiting 1.5, defects 1.5, inventory 1, unnecesary 0.6 and overproduction 0. There are Non Value Added Activities (NVA) ) of the entire product manufacturing process is 157s from the analysis of the current state value stream mapping and value stream activity which has the largest percentage is value added with a percentage of 46%, while for non value added with a percentage of 29.10% and the smallest percentage is necessary but non-value added by 22.53%. Key word : Kaizen, Lean Manufacturing, Value Stream Mapping